2022
DOI: 10.12998/wjcc.v10.i22.7772
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of multiple abnormal genes in non-small-cell lung cancer

et al.

Abstract: BACKGROUND Non-small-cell lung cancer (NSCLC) has the highest morbidity and mortality rates among all malignant tumor types. Although therapies targeting the mutated genes such as KRAS have been used in the clinic for many years, the prognosis remains poor. Therefore, it is necessary to further study the aberrant expression or mutation of non-target genes affecting the survival and prognosis. AIM To explore the impact of simultaneous abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Investigations have been conducted to verify whether the type of gene mutation influences the prognostic and predictive effect of TP53 mutations. Anchored to mutations subtypes, TP53 mutations showed a remarkable preference for missense mutations over nonsense and frameshift mutations, which are commonly dominant in other tumor suppressor genes such as RB1 and PTEN ( 24 ). The study from Labbé et al ( 6 ) showed that NSCLC patients with TP53 missense mutations have significantly shorter PFS when treated with target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have been conducted to verify whether the type of gene mutation influences the prognostic and predictive effect of TP53 mutations. Anchored to mutations subtypes, TP53 mutations showed a remarkable preference for missense mutations over nonsense and frameshift mutations, which are commonly dominant in other tumor suppressor genes such as RB1 and PTEN ( 24 ). The study from Labbé et al ( 6 ) showed that NSCLC patients with TP53 missense mutations have significantly shorter PFS when treated with target therapy.…”
Section: Discussionmentioning
confidence: 99%